Teaching Vocabulary Through Storytelling to Kindergarten Students from a Public School in Dosquebradas (2022)
The following classroom project describes the implementation of storytelling to teach English vocabulary to kindergartners. This project was developed at a public school in Dosquebradas, and the implementation was carried out taking into consideration that vocabulary is important in the process of learning a second language. This classroom project was based on the Engage, Study and Active model, to determine the effectiveness of the use of storytelling to teach vocabulary in a fun and significant manner, helping kindergartners to improve their second language and imagination. High participation and understanding about the topics developed in the classes were shown in the results, but also some disruptive behavior and issues with the use of L1 were evidenced during the implementation of this project.